Comparison of GFR Values Measured with Different Methods and the Relative Renal Functions in Patients with Proven or Suspected Obstructive Uropathy - Demir, Fadime; Balci, Tansel Ansal; Simsek, Fikri Selcuk; Demir, Mustafa (Aves, 2020)
Objective: We compared the glomerular filtration rate (GFR) values as measured by the gamma camera and eGFR methods, calculated by the Modification of Diet in Renal Disease (MDRD) and Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) formula in patients who underwent diethylenetriamine penta-acetic acid (DTPA) dynamic renal scintigraphy for suspected obstructive uropathy. Materials and Methods: A total of 59 patients were included in this retrospective study. On the basis of the eGFR results, patients were divided into three groups; eGFR >90 mL min-1 (Group 1), 60-90 mL min-1 (Group 2), and <60 mL min-1 (Group 3). The groups were compared in terms of GFR measuring methods, percentage of reduction in relative renal function, and pathologic findings detected in radiological imaging methods. Results: We found that eGFR values calculated by CKD-EPI formula were slightly more compatible with GFR values measured by the camera method compared with eGFR values calculated by MDRD formula (mean difference of -17 and -21 respectively, at Bland-Altman plot). We also showed that although there was no decrease in eGFR values, we could show relative function in any kidney under 30% by the scintigraphic method (in 14 patients). Conclusion: The camera method can be used as an alternative for GFR measurement, but it should be noted that it may be slightly higher than the values calculated by the formula. In addition, it should be kept in mind that there may be a decrease in relative renal function values of the kidneys even if GFR values are normal in patients with obstructive uropathy.
14th Congress of the Balkan-Cities-Association-of-Nephroogy-Dialysis-Transplantation-and-Artificial-Organs -- SEP 20-23, 2018 -- Budva, MONTENEGRO
Keywords: Dynamic renal scintigraphy; glomerular filtration rate; obstructive uropathy